Risk Factors and Prevalence of mcr-1-Positive Escherichia coli in Fecal Carriages Among Community Children in Southern Taiwan - Wu, Pin-Chieh; Cheng, Ming-Fang; Chen, Wan-Ling; Hung, Wan-Yu; Wang, Jiun-Ling; Hung, Chih-Hsin (Frontiers in Microbiology, 2021)
Colistin is the last resort antimicrobial for treating multidrug-resistant gram-negative bacterial infections. The plasmid-mediated colistin resistance gene, mcr-1, crucially influences colistin’s resistance transmission. Human fecal carriages of mcr-1-positive Escherichia coli were also detected in many regions worldwide; however, only a few studies have focused on children. Therefore, we identified the prevalence and risk factors of mcr-1-positive Escherichia coli in fecal carriages among community children in Southern Taiwan. In this study, 510 stool samples were collected from April 2016 to August 2019 from the pediatric department at a medical center in Southern Taiwan. These samples were collected within 3 days after admission and were all screened for the presence of the mcr-1 gene. Diet habits, travel history, pet contact, and medical history were also obtained from participants to analyze the risk factors of their fecal carriages to mcr-1-positive Escherichia coli. Antimicrobial susceptibility testing was determined using the VITEK 2 system and the broth microdilution test. Twelve mcr-1-positive Escherichia coli was isolated from 2.4% of the fecal samples. Through multivariate analysis, frequent chicken consumption (at least 3 times per week) had a significantly positive association with the presence of mcr-1-positive E. coli in fecal carriages (adjust odds ratio 6.60, 95% confidence interval 1.58– 27.62, p = 0.033). Additionally, multidrug resistance was more common in mcr-1-positive Escherichia coli (75.0% vs. 39.5%, p = 0.031) than in non-mcr-1-positive Escherichia coli. Furthermore, the percentage of extraintestinal pathogenic Escherichia coli in mcr-1-positive isolates was 83.3%. Some sequence types in our mcr-1-positive Escherichia coli were also similar to those isolated from food animals in the literature. The prevalence of fecal carriages of mcr-1-positive Escherichia coli was low among community children in Southern Taiwan. Our data shows that chicken consumption with a higher frequency increases the risk of mcr-1-positive Escherichia coli in fecal carriages.